2019
DOI: 10.17140/aftnsoj-5-156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Varieties of Pea under AgroClimatic Conditions of Gilgit-Baltistan

Abstract: Materials and Methods Five pea varieties were evaluated for their performance at mountain agricultural research centre (MARC), Juglote, Gilgit during 2017. The varieties are climax, pasan, rondo, meteor and green feast. Results Differences among plant heights of pea varieties were significant with maximum plant height of 85.25 cm noted in plots of variety climax, while the minimum plant height of 45.75 cm was recorded in plots of variety rondo. Number of branches per plant of the different varieties ranged sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…We reported the highest green pod yield (233.1 g plant -1 ) whereas Ei-dakkak (2016) reported the maximum green pod yield (215.3 g plant -1 ). Differences in green pod yield in pea genotypes were also reported by many researchers (Khichi et al 2017, Poudel et al 2017, Din et al 2019and Luitel et al 2021. Significant differences in PM disease, seed number pod -1 , dry pod number plant -1 , dry seed weight plant -1 , hundred seed weight and seed yield were observed in pea genotypes (Table 4, Table 5, and Table 6).…”
Section: Discussionsupporting
confidence: 74%
“…We reported the highest green pod yield (233.1 g plant -1 ) whereas Ei-dakkak (2016) reported the maximum green pod yield (215.3 g plant -1 ). Differences in green pod yield in pea genotypes were also reported by many researchers (Khichi et al 2017, Poudel et al 2017, Din et al 2019and Luitel et al 2021. Significant differences in PM disease, seed number pod -1 , dry pod number plant -1 , dry seed weight plant -1 , hundred seed weight and seed yield were observed in pea genotypes (Table 4, Table 5, and Table 6).…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, the highest (12.5 t/ha) pod yield was recorded in HRSDGP-11-18-1, followed by HRSDGP-11-18-11 (12.3 t/ha) and HRSDGP-11-18-2 (12.1 t/ha) and the lowest (8.2 t/ha) was measured in HRSDGP-11-18-9. Significant (p ≤ 0.05) differences in fresh pod yield in pea genotypes have reported by many researchers (Khichi et al, 2017;Din et al, 2019;Luitel et al, 2023). Poudel et al (2017) have reported the highest fresh pod yield (18.14 t/ha) in DGP-09, but this study found the highest fresh pod yield (12.5 t/ha) in HRSDGP-11-18-1.…”
Section: Pod Weight and Fresh Pod Yieldmentioning
confidence: 49%